THE ANALYSIS OF METAPHORS IN MEDIA TEXTS - Sagatova Muborak Payzidinovna (Western European Studies, 2024)
Metaphors are a fundamental aspect of human language and cognition, allowing individuals to understand and convey complex ideas through the lens of more familiar or concrete experiences. In media texts—whether in print, television, online platforms, or advertising—metaphors play a crucial role in shaping narratives, influencing public perception, and persuading audiences. This article explores the role of metaphors in media texts, examining how they are used, their impact on communication, and the methods of analysis that can unveil their hidden meanings and implications.
Keywords: metaphors; concept; discourse analysis